Vertical Garden Training As A Mean Of Increasing Awareness For The Environment Of Duwet Village, Andong District, Boyolali Regency - Riyadi, Slamet; Jodhi, Achmad; Karim, Ahmad; Zhafirah, Andhita; Murniati, Murniati (PHEDHERAL, 2021)
The planting training activity with the vertical garden technique at Dukuh Duwet is one of the community service activities carried out by the KKN UNS 97 group. This activity was held on 20 February 2021 offline in Dukuh Duwet. The main targets of this activity are housewives and the general public. The purpose of this activity is as a persuasion movement to the community, especially mothers, about the importance of preserving the beauty and comfort of the surrounding community, as well as a movement for the processing and utilization of plastic waste. The socialization activities were also accompanied by practical activities in the field, namely the provision of plant seeds in the form of vegetables, which were then carried out for each of them. This activity method is non-formal, interactive, and interesting so that it is easy to understand. In addition, the materials and methods of making a vertical garden are easy to find in the neighborhood. The result of this work program is that the community can participate well and enthusiastically. This activity is also meant to inspire the participants to take it more seriously on a larger scale with a wider benefit.